Heat-treatment effects on mechanical properties and microstructure evolution of Ti-6Al-4V alloy fabricated by laser powder bed fusion - Tsai, Min-Tsang; Chen, Yi-Wen; Chao, Chih-Yeh; Jang, Jason S.C.; Tsai, Chih-Ching; Su, Yu-Lun; Kuo, Che-Nan (Journal of alloys and compounds, 2020)
Recently, the Ti-6Al-4V alloy fabricated by laser powder bed fusion has been widely studies. According to the high cooling rate, the strength of 3D printed Ti-6Al-4V alloy usually higher than that made by traditional process. In the meanwhile, the residual stress or microstructure feature that caused by high cooling rate usually causes the lower ductility. Therefore, such defects of these Ti-based alloys should be prevented before the application. Besides the porosity, the overall ductility of Ti-based alloys is consisted of its microstructure, of which dominated by acicular α′ structure with some dislocations or twins. Namely, an important effect on ductility is the α′ phase decomposed into the α phase and β phase. In present researches, some various heat treatment conditions are performed, and to investigate the relationship between their microstructures and mechanical properties. By proper heat treatment, the temperature of martensitic transition (Ms) temperature was between 750 and 800 °C, which is lower than the traditional cast/wrought Ti-6Al-4V alloy. Moreover, through the identification of XRD and TEM, there is a α’→α + β transformation and some island β-phase particles formed at the acicular α phase interface. It is also shown that the residual stress can be eliminated after annealed at 600 °C for various times resulting to increase the overall elongation about 3–5% without significantly reducing the strength. •The selective laser melting (SLM) method is adopted to fabricate Ti-6Al-4V materials.•The relationship between heat treatment parameter, microstructure, and mechanical properties of LPBF Ti-6Al-4V is explored.•The suggested heat treatment parameter are proposed and evaluated.